Protected areas in Central Mexico - are they fit in promoting species persistence under climate and land use changes? - Alagador, Diogo (2021)
Protected areas are among the most widely accepted methods to set aside biodiversity from their most impinging threats. However, protected areas are not always located such that their positive impacts over biodiversity are maximized. This drawback is especially significant and uncontrolled when intense climate-change dynamics stresses local biodiversity equilibrium. This study aims to weight plausible evolutive scenarios (up to 2040) of PA-effectiveness to secure the most suitable climates for 94 vertebrate species in Central Mexico, a region that, historically, has faced large biodiversity turnover rates. Effectiveness was appraised at two scales. For a set of species, effectiveness expresses the spatial matching of established protected areas (ePAs) with top priority areas (T17) obtained from an optmised area-selection protocol. For each single species, effectiveness relates the predicted trends of climate suitable areas within ePAs/T17 with trends outside ePAs/T17. Results show that aprox.54% of ePAs area occur within T17 and species present variable responses, with suitability gains up to 10% and potential climate suitability losses of aprox.30% within ePAs. A considerable high amount of T17 (aprox.74%) is left unprotected. By assuming the high-valued component of past conservation efforts, this study delivers a double-guidance for planners and decision-makers. First, it pinpoints the ePAs that will demand further conservation investments in the upcoming years. Second, it identifies the unprotected regions where most active conservation actions are needed to supplement ePAs for a climate-effective protected area network. The framework here-proposed gives decision-makers the means to undertake effective and robust decisions in a dynamic and uncertain world.